2012
DOI: 10.1002/adsc.201200375
|View full text |Cite
|
Sign up to set email alerts
|

[3+2] Cycloaddition of Propargylamines and α‐Acylketene Dithioacetals: A Synthetic Strategy for Highly Substituted Pyrroles

Abstract: A new [3+2] cycloaddition strategy for the direct synthesis of highly substituted pyrroles from the readily available α‐acylketene dithioacetals (or related substrates) and commercially available propargylamines under mild metal‐free conditions has been developed. In this reaction, the acyl group plays a critical role in driving the conjugate addition of propargylamine and further cyclization to give pyrroles. Furthermore, the wide scope was confirmed by the preparation of 1,2,3,4‐tetrasubstituted pyrroles (60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The authors reacted a series of N-propargylamines 466 with α-acylketene dithioacetals 467 in DMF, and pyrroles 468 were obtained in high-excellent yields (Scheme 100). 288 The proposed mechanism of the reaction involves a 1,4-Michael addition between 466 and 467 leading first to the intermediate 469, which is in equilibrium with 470. In the presence of a base, the imine 470 undergoes intramolecular 5exo-dig cyclization affording the intermediate 471 which is converted into the desired pyrroles 468 via a deacetylation and aromatization sequence.…”
Section: Miscellaneous Metal-free Synthesis Of Pyrrolesmentioning
confidence: 99%
“…The authors reacted a series of N-propargylamines 466 with α-acylketene dithioacetals 467 in DMF, and pyrroles 468 were obtained in high-excellent yields (Scheme 100). 288 The proposed mechanism of the reaction involves a 1,4-Michael addition between 466 and 467 leading first to the intermediate 469, which is in equilibrium with 470. In the presence of a base, the imine 470 undergoes intramolecular 5exo-dig cyclization affording the intermediate 471 which is converted into the desired pyrroles 468 via a deacetylation and aromatization sequence.…”
Section: Miscellaneous Metal-free Synthesis Of Pyrrolesmentioning
confidence: 99%
“…In our recent research, we found that reaction of 86a with commercially available propargylamine in DMF in the absence of an external base can afford 88a in good yield (Scheme ). In the presence of DBU (1,8-diazabicyclo[5.4.0]­undec-7-ene) as the external base, both 88a and 89a were obtained.…”
Section: Heteroannulation Reactions Via Ketene Ns-acetalsmentioning
confidence: 99%
“…It is noted that when external N-propargylamines (R 1 ¼ H) were used as substrates, the reaction was performed in the absence of an external base and the corresponding products were obtained in high to excellent yields. 7 Recently, Jin and co-workers demonstrated that polysubstituted pyrroles 16 can be readily prepared in the reaction of N-propargylamines 14 with activated alkynes 15 in the presence of 20 mol% of K 3 PO 4 as catalyst in DMSO at 120 C (Scheme 6) The authors suggested that the reaction proceeds via the formation of N-propargylic b-enaminoester intermediates A through Michael addition of N-propargylamines 14 to alkynes 15, which aer a 5-exo-dig cyclization process delivers the 3carboxylated pyrroles 16 in good yields. 8 Later, Zhang's research team reported a direct synthesis of polysubstituted pyrrole derivatives 18 via base-catalyzed intramolecular cyclization of N-propargylic b-enaminones 17 (Scheme 7).…”
Section: Pyrrolesmentioning
confidence: 99%